Brief Communication: Rotation of the Maxillary Premolars: Evidence in Support of Premolar Morphogenetic Field - Vincent H. Stefan (Dental Anthropology Association, 2006)
The presence of an individual tooth, axially rotated within the maxillary and/or mandibular dental arcade is not an uncommon occurrence in the human dentition. Far rarer is the axial rotation of two or more adjacent teeth, rotated together as a "unit" within the dental arcade. Two rare cases are presented here, each case possessing a maxillary P3-P4 unit that has been axially rotated. This event is in and of itself interesting and important, yet it also potentially provides support for the concept of a "premolar" morphogenetic field.